2022
DOI: 10.1021/acsnano.2c07895
|View full text |Cite
|
Sign up to set email alerts
|

Light-Triggered Self-Assembly of Peptide Nanoparticles into Nanofibers in Living Cells through Molecular Conformation Changes and H-Bond Interactions

Abstract: Controlled self-assembly has attracted extensive interest in biological and nanotechnological applications. Enzymatic or biocatalytic triggered self-assembly is widely used for the diagnostic and prognostic marker in different pathologies because of their nanostructures and biological effects. However, it remains a great challenge to control the self-assembly of peptides in living cells with a high degree of spatial and temporal precision. Here we demonstrate a lighttriggered platform that enables spatiotempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…41 Currently, the in vivo self-assembly of peptides is typically achieved through endogenous stimuli, such as enzymes, pH, and redox reactions in specific physiological and pathological regions, or exogenous stimuli, such as light, sound, and temperature. [42][43][44][45][46][47][48] In recent years, numerous reviews have been published on the in vivo self-assembly strategies of stimuli-responsive peptides and their biomedical applications in areas such as tumor therapy, drug delivery, and antibacterial treatments. [49][50][51][52][53] However, under complex physiological conditions in vivo, due to the dynamic characteristics of selfassembled nanomaterials, changes in their morphology and structure in response to stimuli will affect their performance on the biological surface.…”
Section: Yimentioning
confidence: 99%
See 1 more Smart Citation
“…41 Currently, the in vivo self-assembly of peptides is typically achieved through endogenous stimuli, such as enzymes, pH, and redox reactions in specific physiological and pathological regions, or exogenous stimuli, such as light, sound, and temperature. [42][43][44][45][46][47][48] In recent years, numerous reviews have been published on the in vivo self-assembly strategies of stimuli-responsive peptides and their biomedical applications in areas such as tumor therapy, drug delivery, and antibacterial treatments. [49][50][51][52][53] However, under complex physiological conditions in vivo, due to the dynamic characteristics of selfassembled nanomaterials, changes in their morphology and structure in response to stimuli will affect their performance on the biological surface.…”
Section: Yimentioning
confidence: 99%
“…80,81 When the assembled peptide interacts with the protein, multiple hydrogen bonds formed between the amide bonds of the peptide main chain and each side chain group form a hydrogen bond array, inducing the orientation of the overall and active center of the protein. 45,82 This provides a basis for constructing protein assemblies with precise orientation. Eisenberg et al demonstrated that short peptide fragments with a β-sheet structure in amyloid can specifically co-assemble with the corresponding amyloid, driving the protein to transition from the native structure to the amyloid state.…”
Section: Interaction Between Peptide Nanomaterials and Biological Int...mentioning
confidence: 99%
“…Sun et al reported a photoactivated system that allows precise manipulation of the arrangement of nanoparticles (NPs) into nanofibers within living cells by utilizing subtle alterations in molecular conformation and internal hydrogen bonding interactions. [ 58 ] The results indicate that the use of light‐induced controllable assembly can be employed to actively regulate cellular behaviors in living organisms. Nieland et al demonstrated the creation of various dissipative or metastable dynamic covalent systems by utilizing photons as a trigger, enabling manipulation of the quantity of monomers engaged in cyclo‐oligomerization, resulting in both ring contraction and expansion.…”
Section: Modulation Of Chirality In Supramolecular Self‐assembly Proc...mentioning
confidence: 99%
“…The cellular environment is rich in biological macromolecules and reactive species, which inspires chemists to artificially perform various chemical reactions in cells for physiological purposes. Among all of these artificial reactions, intracellular chemical polymerization represents a sparkling frontier. Small monomers can undergo in situ polymerization in a miniature “lab”, achieving prolonged retention for the products and adequately regulating cell behavior. Despite a few studies based on intracellular polymerization, such as radical polymerization, condensation polymerization, and electroactive polymerization, conducting polymerization inside living cells remains an appealing yet significantly challenging task. For instance, abundant oxygen and amino acids in cells may inevitably cause side reactions and even quench the polymerization process.…”
Section: Introductionmentioning
confidence: 99%